2022
DOI: 10.1200/op.21.00170
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Workplace Drivers of Burnout in Cancer Care Physicians in Ontario, Canada

Abstract: PURPOSE: Provider well-being has become the fourth pillar of the quadruple aim for providing quality care. Exacerbated by the global COVID-19 pandemic, provider well-being has become a critical issue for health care systems worldwide. We describe the prevalence and key system-level drivers of burnout in oncologists in Ontario, Canada. METHODS: This is a cross-sectional survey study conducted in November-December 2019 of practicing cancer care physicians (surgical, medical, radiation, gynecologic oncology, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…In general, those professionals up to 30 years of age were more likely to have Burnout syndrome (p = 0.000000165), with the prevalence decreasing with increasing age. Similarly, in the study by Khan et 2020), observed higher scores on the GAD − 7 scale for anxiety among those younger, between 25 and 44 years old, so those over 45 years old were less likely to experience anxiety symptoms (p = 0.011) [5,[8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…In general, those professionals up to 30 years of age were more likely to have Burnout syndrome (p = 0.000000165), with the prevalence decreasing with increasing age. Similarly, in the study by Khan et 2020), observed higher scores on the GAD − 7 scale for anxiety among those younger, between 25 and 44 years old, so those over 45 years old were less likely to experience anxiety symptoms (p = 0.011) [5,[8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 77%
“…Inventory (CBI) to assess the prevalence among primary care physicians during the pandemic, high levels of BS were found for the 3 domains: 65.9% with personal burnout, 68.7% for Work-related burnout and 54.7% for patient-related burnout. In the study by Civantos et al (2020), who used the Mini-Z for head and neck surgeons, the prevalence was 14.7% [5,[8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…We have gathered enough evidence in healthcare to know what is driving poor wellbeing, and how these processes impact on quality of care and patient safety (6). Indeed, there is a plethora of studies on the drivers of burnout (7)(8)(9), the mechanisms of burnout (10-13) and reviews of burnout interventions in healthcare (14)(15)(16)). Thus, it could be argued that we have a good idea of what we need to do to improve the situation.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the onset of the COVID-19 pandemic, several studies had already reported elevated burnout levels amongst various groups of healthcare workers (e.g. , 4 ; 6 ; 25 ; 27 ; 30 . Globally, research showed that as the COVID-19 pandemic progressed, burnout continued to be a significant problem impacting healthcare workers 11 ; 15 , and in some cases had become present at higher rates than previously reported 17 .…”
Section: Introductionmentioning
confidence: 99%